Application of Lurian Approach to Assessment of Perpetrators of Crimes - Kaczmarek, B (KnE Life Sciences, 2018)
The central question in law is whether a defendant is responsible for his/her wrongdoing. Recent progress in neuroscience, especially in brain imaging, has shown potential for finding more objective tools for the evaluation of brain disorders. In the case of perpetrators, damage to the prefrontal area is believed to be of relevance in criminal responsibility, since it modulates and controls aggressive urges originating from the limbic system. To absolve guilt, a brain scan would have to show that a perpetrator was unable to control his/her behavior; however, it shows only what is and not what could be. It is therefore impossible to obtain behavioral data that would indicate a disorder of executive functioning at both the time of evaluation and the instant offence. The diagnostic value of performing a neurolinguistics analysis of narratives elicited from brain-damaged patients was demonstrated in the first study. Another study supported the assumption of a frontal lobe defect in individuals with a history of violent behavior. The present study compared results obtained from three groups matched for age, sex, and education: perpetrators of crimes, healthy soldiers, and patients with lesions of the frontal lobes. A battery of tests measuring frontal lobe deficits was administered along with one of the tasks of the Narrative Abilities Test, based upon Luria’s approach to the examination of speech. Statistically significant differences were found between perpetrators and healthy controls but not between frontal lobe patients and perpetrators, which confirms frontal lobe deficits in that group. Keywords: Lurian approach, perpetrators, neurolinguistics analysis, narratives